Optimal Systolic Blood Pressure Levels for Primary Prevention of Stroke in General Hypertensive Adults: Findings From the CSPPT (China Stroke Primary Prevention Trial). Issue 4 (April 2017) - Fan, Fangfang; Yuan, Ziwen; Qin, Xianhui; Li, Jianping; Zhang, Yan; Li, Youbao; Yu, Tao; Ji, Meng; Ge, Junbo; Zheng, Meili; Yang, Xinchun; Bao, Huihui; et al.
Abstract : We aimed to investigate the relationship of time-averaged on-treatment systolic blood pressure (SBP) with the risk of first stroke in the CSPPT (China Stroke Primary Prevention Trial). A post hoc analysis was conducted using data from 17 720 hypertensive adults without cardiovascular disease, diabetes mellitus, and renal function decline from the CSPPT, a randomized double-blind controlled trial. The primary outcome was first stroke. Over a median follow-up duration of 4.5 years, the association between averaged on-treatment SBP and risk for first stoke followed a U-shape curve, with increased risk above and below the reference range of 120 to 130 mm Hg. Compared with participants with time-averaged on-treatment SBP at 120 to 130 mm Hg (mean, 126.2 mm Hg), the risk of first stroke was not only increased in participants with SBP at 130 to 135 mm Hg (mean, 132.6 mm Hg; 1.5% versus 0.8%; hazard ratio, 1.63; 95% confidence interval, 1.01–2.63) or 135 to 140 mm Hg (mean, 137.5 mm Hg; 1.9% versus 0.8%; hazard ratio, 1.85; 95% confidence interval, 1.17–2.93), but also increased in participants with SBP <120 mm Hg (mean, 116.7 mm Hg; 3.1% versus 0.8%; hazard ratio, 4.37; 95% confidence interval, 2.10–9.07). Similar results were found in various subgroups stratified by age, sex, and treatment group. Furthermore, lower diastolic blood pressure was associated with lower risk of stroke, with a plateau at a time-average on-treatment diastolic blood pressure <80 mm Hg. In conclusion, among adults with hypertension and without a history of stroke or myocardial infarction, diabetes mellitus, or renal function decline, a lower SBP goal of 120 to 130 mm Hg, as compared with a target SBP of 130 to 140 mm Hg or <120 mm Hg, resulted in the lowest risk of first stroke. Abstract : Supplemental Digital Content is available in the text.